Mitochondrial quality control mechanisms as molecular targets in cardiac ischemia–reperfusion injury - Wang, Jin; Zhou, Hao (Acta pharmaceutica Sinica. B, 2020)
Mitochondrial damage is a critical contributor to cardiac ischemia/reperfusion (I/R) injury. Mitochondrial quality control (MQC) mechanisms, a series of adaptive responses that preserve mitochondrial structure and function, ensure cardiomyocyte survival and cardiac function after I/R injury. MQC includes mitochondrial fission, mitochondrial fusion, mitophagy and mitochondria-dependent cell death. The interplay among these responses is linked to pathological changes such as redox imbalance, calcium overload, energy metabolism disorder, signal transduction arrest, the mitochondrial unfolded protein response and endoplasmic reticulum stress. Excessive mitochondrial fission is an early marker of mitochondrial damage and cardiomyocyte death. Reduced mitochondrial fusion has been observed in stressed cardiomyocytes and correlates with mitochondrial dysfunction and cardiac depression. Mitophagy allows autophagosomes to selectively degrade poorly structured mitochondria, thus maintaining mitochondrial network fitness. Nevertheless, abnormal mitophagy is maladaptive and has been linked to cell death. Although mitochondria serve as the fuel source of the heart by continuously producing adenosine triphosphate, they also stimulate cardiomyocyte death by inducing apoptosis or necroptosis in the reperfused myocardium. Therefore, defects in MQC may determine the fate of cardiomyocytes. In this review, we summarize the regulatory mechanisms and pathological effects of MQC in myocardial I/R injury, highlighting potential targets for the clinical management of reperfusion. Mitochondrial quality control contributes to acute cardiac I/R injury. The mitochondrial network is constantly reshaped by the antagonistic activities between mitochondrial fission and fusion. Mitophagy allows autophagosomes to selectively degrade damaged mitochondria. When these adaptive responses fail, programmed cell death by apoptosis or necroptosis is activated. [Display omitted]